Automatic electronic reporting improved the completeness of AMI and stroke incident surveillance in Tianjin, China: a modeling study - Hong Xiao; Fang Liu; Joseph M. Unger (BMC, 2023)
Abstract Background AMI and stroke are the leading causes of premature mortality and hospitalizations in China. Incidence data at the population level for the two diseases is limited and the reliability and completeness of the existing incidence registry have not been investigated. We aim to assess if the completeness of case ascertainment of AMI and stroke incidence has improved since the implementation of electronic reporting and to estimate the incidence of AMI and stroke in Tianjin, China. Methods We applied the DisMod II program to model the incidence of AMI and stroke from other epidemiological indicators. Inputs include mortality rates from Tianjin's mortality surveillance system, and the point prevalence, remission rates and relative risks taken from IHME's Global Burden of Disease studies. The completeness of AMI and stroke incidence reporting was assessed by comparing the sex and age-specific incidence rates derived from the incidence surveillance system with the modeled incidence rates. Results The age and sex standardized modeled incidence per 100,000 person-year decreased (p < 0.0001) from 138 in 2007 to 119 in 2015 for AMI and increased (p < 0.0001) from 520 in 2007 to 534 in 2015 for stroke. The overall completeness of incidence report was 36% (95% CI 35-38%) for AMI and 54% (95% CI 53-55%) for stroke. The completeness was higher in men than in women for both AMI (42% vs 30%, p < 0.0001) and stroke (55% vs 53%, p < 0.0001) and was higher in residents aged 30-59 than those aged 60 or older for AMI (57% vs 38%, p < 0.0001). The completeness of reporting increased by 7.2 (95% CI 4.6-9.7) and 15.7 (95% CI 14.4-16.9) percentage points for AMI and stroke, respectively, from 2007 to 2015 among those aged 30 or above. The increases were observed in both men and women (p < 0.0001) and were more profound (p < 0.0001) among those aged between 30 and 59 and occurred primarily during the 2010 and 2015 period. Conclusions Completeness of AMI and stroke incidence surveillance was low in Tianjin but has improved in recent years primarily owing to the incorporation of an automatic reporting component into the information systems of health facilities.